A Conceptual Paper of Risk Industry Moderation: Sustainable Growth, Intellectual Capital, and Firm Value Dynamics - Fatikhatur Rohmah; Muhammad Ja’far Shodiq (Universitas Darussalam Gontor, 2024)
This research investigates the impact of industry risk barriers on the relationship between intellectual capital and sustainable growth rate on firm value. The focus of this study is on companies listed in the LQ45 Index on the Indonesia Stock Exchange during the 2020-2022 period. The research uses quantitative methods with an explanatory research design. Data was taken using a purposive sampling technique, and data analysis was carried out using Moderated Regression Analysis (MRA). It is hoped that the findings of this research will contribute to the understanding of the role of industry risk barriers as a moderating variable in influencing the relationship between intellectual capital, sustainable growth rates, and firm value. The results of the analysis are expected to provide insight for stakeholders, especially company policymakers, to identify factors that can influence firm value more effectively. It is hoped that the conclusions of this research can be the basis for developing better risk management strategies in optimizing firm value amidst ever-changing market dynamics.